2014
DOI: 10.1530/eje-13-0790
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid autoantibodies per se do not impair intracytoplasmic sperm injection outcome in euthyroid healthy women

Abstract: Objective: Autoimmune thyroid disease (AITD) has been associated with adverse pregnancy outcomes in subfertile women with spontaneous and assisted reproductive technology-induced pregnancies. The underlying pathophysiology is still elusive and an association with thyroid dysfunction or other infertility causes is discussed. However, whether thyroid autoimmunity (TAI) per se has a negative impact on female fertility has not yet been clarified. In this study, we investigated whether TAI in healthy women undergoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 21 publications
2
34
0
1
Order By: Relevance
“…However, a recent metaanalysis by Poppe et al failed to demonstrate this effect (OR = 0.95, p = 0.31) [25]. The total events and studies [19,27].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, a recent metaanalysis by Poppe et al failed to demonstrate this effect (OR = 0.95, p = 0.31) [25]. The total events and studies [19,27].…”
Section: Discussionmentioning
confidence: 97%
“…We also did not find any significant differences between ATA-positive and ATAnegative patients regarding the ongoing pregnancy rate. Some studies assessed the live birth rate, and most of them did not establish any significant difference in ATA-positive patients in comparison with ATA-negative patients [23,25,27]. Conversely, a meta-analysis reported a lower live birth rate with an OR = 0.65 (p = 0.004) in thyroid autoimmunity [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They presented a plea for further research that would look at the process of fertilization aiming at discovering other factors related to it. Tan et al [45] have looked at the outcome of ICSI in relation to thyroid antibodies and found that serology results did not affect the process of ICSI. This study included a series of 835 women.…”
Section: Thyroid Function Thyroid Antibodies and Fertilitymentioning
confidence: 99%
“…A randomized controlled trial by Negro et al (2010) first reported that levothyroxine (L-T4) intervention that fertilization, pregnancy rate and live birth rate are lower in TPOAb-positive infertile women undergoing ART, but others do not [15][16][17][18]. TAI is associated with hypothyroidism, so it is unclear whether TAI itself or the subsequent thyroid dysfunction adversely affects pregnancy.…”
mentioning
confidence: 99%